New Worlds from Below: Informal life politics and grassroots action in twenty-first-century Northeast Asia - Morris-Suzuki, Tessa; Jeong Soh, Eun (ANU Press, 2017)
In Asia today, the grand ideologies of the past have lost their power over the popular imagination. Even in many of the region's democracies, popular engagement in the political process faces profound challenges. Yet amidst this landscape of political disenchantment, groups of ordinary people across Asia are finding new ways to take control of their own lives, respond to threats to their physical and cultural survival, and build better futures. This collection of essays by prominent scholars and activists traces the rise of a quiet politics of survival from the villages of China to Japan's Minamata and Fukushima, and from the street art of Seoul and Hong Kong to the illegal markets of North Korea. Introducing an innovative conceptual framework, New Worlds from Below shows how informal grassroots politics in Northeast Asia is generating new ideas and practices that have region-wide and global relevance.